The correlation of genotype and phenotype in Portuguese hyperphenylalaninemic patients - Rivera, I (2015)
To understand the basis for the clinical heterogeneity of phenylalanine hydroxylase deficiency among Portuguese hyperphenylalaninemic patients, genotype-phenotype correlations were established. A group of 61 patients was completely genotyped, leading to t